A Novel Multifunctional 5,6-Dimethoxy-Indanone-Chalcone-Carbamate Hybrids Alleviates Cognitive Decline in Alzheimer’s Disease by Dual Inhibition of Acetylcholinesterase and Inflammation - Liu, Chan; Sang, Zhipei; Pan, Hong; Wu, Qin; Qiu, Yu; Shi, Jingshan (Frontiers in Aging Neuroscience, 2022)
Backgrounds: Alzheimer's disease (AD) is a multifactorial neurodegenerative disease. The treatment of AD through multiple pathological targets may generate therapeutic efficacy better. The multifunctional molecules that simultaneously hit several pathological targets have been of great interest in intervention of AD. Methods: Here we combined the chalcone scaffold with carbamate moiety and 5,6-dimethoxy-indanone moiety to generate a novel multi-target-directed ligand (MTDL) molecule(E)-3-((5,6-dimethoxy-1-oxo-1,3-dihydro-2H-inden-2-ylidene)-methyl)phenylethyl(methyl) carbamate (named AP5). In silico approaches were used to virtually predict the binding interaction of AP5 with AChE, the drug-likeness and BBB penetrance, and later validated by evaluation of pharmacokinetics (PK) in vivo by LC-MS/MS. Moreover, studies were conducted to examine the potential of AP5 for inhibiting AChE and AChE-induced amyloid-β (Aβ) aggregation, attenuating neuroinflammation and providing neuroprotection in the APP/PS1 model of AD. Results: We found that AP5 can simultaneously bind to the peripheral and catalytic sites of AChE by molecular docking. AP5 exhibited desirable pharmacokinetics (PK) characteristics including oral bioavailability (67.2%), > 10% brain penetrance and favorable drug-likeness. AP5 inhibited AChE activity and AChE-induced Aβ aggregation in vivo and in vitro. Further, AP5 lowered Aβ plaque deposition and insoluable Aβ levels in APP/PS1 mice. Moreover, AP5 exerted anti-inflammatory responses by switching microglia to a disease-associated microglia (DAM) phenotype and preventing A1 astrocytes formation. The phagocytic activity of microglial cells to Aβ was recovered upon AP5 treatment. Importantly, chronic AP5 treatment significantly prevented neuronal and synaptic damage and memory deficits in AD mice. Conclusion: Together, our work demonstrated that AP5 inhibited the AChE activity, decreased Aβ plaque deposition by interfering Aβ aggregation and promoting microglial Aβ phagocytosis, and suppressed inflammation, thereby rescuing neuronal and synaptic damage and relieving cognitive decline. Thus, AP5 can be a new promising candidate for the treatment of AD